2013
DOI: 10.21608/zumj.2013.4320
|View full text |Cite
|
Sign up to set email alerts
|

An Interventional Study to Decrease Central Venous Catheter Related Blood Stream Infection in Intensive Care Units at Zagazig University Hospital

Abstract: Background: Catheter related blood stream infection (CRBSI) is a complication of central venous catheter (CVC) use. This Infection particularly in the ICU population results in higher levels of morbidity and mortality coupled with greater costs in terms of care and increased duration of hospital stay. Aim & Objectives: The aim of this study is to improve the safety of patients with CVC via decreasing the incidence of CRBSI in ICUs patients at Zagazig University Hospital through the following objectives: 1-Calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The Centers for Disease Control and Prevention has published CVC-RI prevention guidelines that help to reduce the rate of CVC-RI and related complications (El Nemr et al, 2015;Ista et al, 2016). Major topics in these guidelines include education of healthcare providers, antisepsis, intravenous administration management, hand hygiene and dressing (Ling et al, 2016;Septimus and Moody, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention has published CVC-RI prevention guidelines that help to reduce the rate of CVC-RI and related complications (El Nemr et al, 2015;Ista et al, 2016). Major topics in these guidelines include education of healthcare providers, antisepsis, intravenous administration management, hand hygiene and dressing (Ling et al, 2016;Septimus and Moody, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An educational interventional study conducted by EL Nemr (2013) including nurses working in surgical units and emergency intensive care units, the results illustrate increase in knowledge level which eventually improved their practices leading to decrease catheter related blood stream infections by 50%. 10 The protocols about strategies to prevent nosocomial infection were not enough in dialysis units. From the results of this study it is evident that only 34.5 % of respondents indicated that they have specific polices to prevent nosocomial infection in dialysis units.…”
Section: Discussionmentioning
confidence: 99%